Clinical researchThe role of aldosterone in myocardial dysfunction of Egyptian patients with essential hypertension - Refaat, Safa; Abd El-Ghaffar, Nagwa; Abd El-Rahman Negm, Hani; Yousri, Tarek (Archives of Medical Science, 2008)
Introduction: Aldosterone is a potent mineralocorticoid. It plays a key role in mediating adverse myocardial remodeling with pressure overload. The aims of this study were to compare the serum levels of aldosterone in well controlled and uncontrolled cases of long standing essential hypertension and correlate these levels to the echocardiographic findings of these patients. Material and methods: Eighty subjects were enrolled in the study: 30 well controlled hypertensives, 30 uncontrolled hypertensives and 20 subjects matched for age and sex as a control group. Results: There was a significant elevation of serum aldosterone level in hypertensive patients which was especially marked in uncontrolled hypertensives compared to the control group. There was a significant positive correlation between aldosterone level and hypertension duration, mean systolic and mean diastolic blood pressure. There was a significant positive correlation between aldosterone level and posterior wall thickness in well-controlled hypertensives and a significant correlation with posterior wall thickness in uncontrolled hypertensives. Aldosterone levels were significantly significant correlated with septal wall thickness only in uncontrolled hypertensives. A significant negative correlation between aldosterone level and fractional shortening percentage, ejection fraction percentage and E/A ratio of left ventricle in controlled and uncontrolled hypertensives was demonstrated. Aldosterone level increase was associated with hypertrophic changes, relative impairment of systolic functions and disturbed diastolic functions that were more significant in uncontrolled hypertensives. Conclusions: Aldosterone receptor blockers should be considered, in the treatment of hypertension to avoid the adverse effects of remodeling on systolic and diastolic function of left ventricle.